2009
DOI: 10.1097/ta.0b013e3181a5f0ed
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Spinal Clearance Protocol for Unconscious Pediatric Trauma Patients

Abstract: There is a need for an evidence-based protocol for the clearance of the spine in the obtunded and high-risk pediatric trauma patient. High-resolution CT with sagittal and coronal reconstructions should be the basis for cervical spinal clearance, in combination with the interpretation of films by an expert radiologist. All spinal regions should be imaged, and clearance should be formally documented. The role of magnetic resonance imaging in routine clearance remains controversial. Multicenter prospective studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…52,53 These are better visualised with MRI. [52][53][54][55][56][57] Therefore some guidelines advise primary imaging screening with radiographs followed by MRI rather than CT, if deemed necessary. 20 Older studies have found as many as 7% of significant neck injuries missed with CT. 58 However some authors argue that spinal injury without CT abnormality in children is very rare and that CT should be the investigation of choice just like in adults.…”
Section: Ionising Radiation: Radiographs and Ctmentioning
confidence: 99%
See 3 more Smart Citations
“…52,53 These are better visualised with MRI. [52][53][54][55][56][57] Therefore some guidelines advise primary imaging screening with radiographs followed by MRI rather than CT, if deemed necessary. 20 Older studies have found as many as 7% of significant neck injuries missed with CT. 58 However some authors argue that spinal injury without CT abnormality in children is very rare and that CT should be the investigation of choice just like in adults.…”
Section: Ionising Radiation: Radiographs and Ctmentioning
confidence: 99%
“…20 Older studies have found as many as 7% of significant neck injuries missed with CT. 58 However some authors argue that spinal injury without CT abnormality in children is very rare and that CT should be the investigation of choice just like in adults. 54 Flexion/extension radiographs, either dynamic or static, in obtunded patients should now be obsolete. They do not reliably show instability and risk worsening neurological compromise.…”
Section: Ionising Radiation: Radiographs and Ctmentioning
confidence: 99%
See 2 more Smart Citations
“…Hutchings et al 17 reviewed c-spine clearance methods retrospectively in 115 consecutive obtunded major trauma patients ,16 years of age. No protocol was used during the 7-year study period.…”
Section: Imagingmentioning
confidence: 99%